Reevaluating the Glorification of Gamification for Unexpected Outcomes in English Language Teaching - Sharizan Sharizan (Balai Bahasa Provinsi Riau, 2023)
This conceptual paper aims to reevaluate the glorification of gamification where it leads to misleading and misconception using gamification in English language teaching. That narrative makes the implementation of the gamification strategy driving to unexpected outcomes. This condition should be addressed and reevaluated. In order to reevaluate the glorification of gamification, several arguments for it are supported by relevant written and spoken resources or studies. The findings show that the readiness of educational actors to the gamified strategy is the biggest problem faced by them and the demand of society and social construction seeing gamification also creates stigma where they must implement gamification learning strategy no matter what. Therefore, the educational actors need to be wise and understanding in implementing and glorifying the gamification strategy in English language teaching.